Effects of Berberine on Atherosclerosis - Rui, Rui; Yang, Haolan; Liu, Yanke; Zhou, Yue; Xu, Xudong; Li, Chaohong; Liu, Shuying (Frontiers in Pharmacology, 2021)
Atherosclerosis is an epidemic across the globe[A1], and its morbidity and mortality remain high, involving various complications and poor prognoses. In atherosclerosis, endothelial cells (ECs) dysfunction, vascular smooth muscle cells (VSMCs) migration and proliferation, foam cell formation, and inflammatory cell recruitment contribute to disease progression. Vascular stem cells (VSCs) also play a critical role in the cardiovascular system. Important data showed that the simultaneous increase of proliferation and apoptosis of VSMCs is the main cause of graft vein stenosis, suggesting that inhibition of VSMCs proliferation and apoptosis simultaneously is an important strategy for the treatment of atherosclerotic stenosis. Complementary and alternative medicine use among patients with cardiovascular disease (CVD) is growing. Berberine is an extract of Chinese traditional herbs that is known for its antimicrobial and anti-inflammatory effects in the digestive system. Its underlying anti-CVD mechanisms are currently attracting interest, and its pharmacological actions, such as antioxidation, regulation of neurotransmitters and enzymes, and cholesterol-lowering effects, have been substantiated. Recent studying found that berberine could inhibit both the proliferation and apoptosis of VSMCs induced by mechanical stretch stress simultaneously, which suggests that berberine might be an excellent drug to treat atherosclerosis. This review will focus on the recent progress of the effect of berberine on vascular cells, especially VSMCs, to provide important data and a new perspective for the application of berberine in anti-atherosclerosis.